FORMATION OF INDICATORS AND CRITERIA FOR ASSESSING THE IMPACT OF RISKS ON AVIATION ACTIVITY - Kharchenko, Volodymyr; Babeichuk, Dmytro; Pechevysty, Ruslan; Alexeiev, Oleh (Proceedings of National Aviation University (archive), 2020)
A feature of modern aviation risk management is the lack of a unified approach to flight safety risk assessment, which is manifested by the fact that different risk measures are used in practice. An effective approach to provide a comprehensive assessment of aviation risks has not yet been proposed. Aviation activities are subject to specific risks, due to their sectoral identity and flight safety features. The article deals with the implementation of a combined approach to preventive management of aviation risks, which requires identification and monitoring of risks under uncertainty.